GAMBARAN STUNTING DI INDONESIA: LITERATUR REVIEW: GAMBARAN STUNTING DI INDONESIA: LITERATUR REVIEW - SULISTYANINGRUM, HASTA; Lita, Anggraini; Wildan, Viedya; Sidabungke, Maria; Rudiansyah, Syahrul (LPPM Universitas Bakti Tunas Husada, 2025)
ABSTRACT Stunting is one of the targets of the Sustainable Development Goals (SDGs), which is included in the second sustainable development goal, namely eliminating hunger and all forms of malnutrition by 2030 and achieving food security. The target set is to reduce the stunting rate to 18.8% by 2025. Stunting can occur as a result of malnutrition, especially during the First 1000 Days of Life (HPK). The method used in this research is to use a literature study with a method of searching, combining essences and analyzing facts from several scientific sources that are accurate and valid. Stunting is a very serious problem because it is associated with a greater risk of morbidity and mortality, obesity and non-communicable diseases in the future, stunting in adulthood, poor cognitive development and lower productivity and income. To prevent stunting, exclusive breastfeeding in the first 6 months, especially for babies from poor families, must be optimized through nutritional education programs and breastfeeding support groups. Furthermore, it is hoped that the results of this literature can be used as additional information to develop further research regarding the picture of stunting in Indonesia. Keywords: Toddlers, Malnutrition, Stunting.